THESOLUTIONSFORTHEAUTOMATIZATIONOFRAILWAYDEPARTMENTSWORKOFINDUSTRIALENTERPRISES - Soltysiuk, O. V.; Yehypko, O. H. (Science and Transport Progress, 2008)
Issues of development of information technologies in the field of creation of approaches for automation of management in operation of railway workshops at industrial enterprises are considered in the paper.